GENERALIZED STUMMEL CLASS AND MORREY SPACES OF NONHOMOGENEOUS TYPE - Budhi, Wono Setya; Sihwaningrum, Idha; Soeharyadi, Yudi (IndoMS, 2014)
In the context of the spaces of nonhomogeneous type, in this paper we study a relation between the generalized Stummel class and the generalized Morrey spaces. The stummel class is a class of functions related to local behavior of mapping by fractional integral operators. Meanwhile, the generalized Morrey spaces are classes of functions related to local behavior of Hardy-Littlewood maximal function. Our results employ the doubling condition of functions under consideration.DOI :Â http://dx.doi.org/10.22342/jims.20.2.187.141-147